Kesulitan Belajar Matematika Materi Pokok Bahasan Bangun Ruang Siswa Kelas IV SDN 26 Mentatai Beloyang - M Lobih, Tressia; Aprima Tirsa; Novika Lestari (STKIP Melawi, 2025)
Abstract: The research is based on the onteraction pattern of teacher and students in learning indonesian in grade 1 of the State Elementary School 28 Kelakik. This study aims to determine the interaction patterns of teachers and students in grade Iand to determine the characteristics of students in the Indonesian language learning process. The research method uses a qualitative descriptive approach. The research subjects were Indonesian language teachers, grade I student and parents. The object of this research is the interaction pattern of teacher and students in learning Indonesian. Data collection techniques using interview sheets, observations sheets. The validity of the data using triangulation of sources, and techniques. The result of the research is the pattern of interaction in Indonesian language learning in grade I of 28 Kelakik Elementary School, which is a one-way interaction, the first grade elementari school teacher conveys the subject matter, the teacher acts as a facilitator by utilizing methods, media and learning resources. Two-way interaction, the teacher conducts questions and answers in learning. Teachers and firts grade elementary school students give each other interacting responses. The characteristics of students in learning are students who like to play, love to do learning activities in groups. The conclusion of the study is the pattern of interaction in learning in grade 1 of 28 Kelakik Elementary School, namely one-way interactions and two-way interaction. Keywords: Interactions, Learning, Indonesian. Abstrak: Penelitian didasari oleh pola interaksi guru dan siswa dalam pembelajaran bahasa Indonsesia di kelas I SD Negeri 28 Kelakik. Penelitian bertujuan mengetahui pola interaksi guru dan siswa di kelas I dan mengetahui karakteristik siswa dalam proses pembelajaran bahasa Indonesia. Metode penelitian menggunakan kualitatif dengan pendekatan deskriptif. Subjek penelitian guru bahasa Indonesia, siswa kelas I dan orangtua siswa. Objek penelitian pola interaksi guru dan siswa dalam pembelajaran bahasa Indonesia. Teknik pengumpulan data menggunakan wawancara, observasi, dokumentasi. Instrumen penelitian menggunakan lembar wawancara, lembar observasi. Keabsahan data menggunakan triangulasi sumber dan teknik. Hasil penelitian adalah pola interaksi dalam pembelajaran bahasa Indonesia pada kelas I SD Negeri 28 Kelakik yaitu terjadi interaksi satu arah, guru kelas I SD menyampaikan materi pelajaran, guru berperan sebagai fasilitator dengan memanfaatkan metode, media dan sumber belajar. Interaksi dua arah, guru melakukan tanya jawab dalam pembelajaran. Guru dan siswa kelas I SD saling memberikan respon berinteraksi. Karakteristik siswa dalam pembelajaran yaitu siswa senang bermain, senang melakukan aktivitas pembelajaran secara berkelompok. Kesimpulan penelitian adalah pola interaksi dalam pembelajaran di kelas I SD Negeri Kelakik yaitu terjadi pola interaksi satu arah dan interaksi dua arah. Kata Kunci: Interaksi, Pembelajaran, Bahasa Indonesia.